Transformation and Deoxyribonucleic Acid Size: Extent of Degradation on Entry Varies with Size of Donor - Morrison, D. A. (1972)
The fate of label introduced as donor deoxyribonucleic acid (DNA) into competent cells of Diplococcus pneumoniae was determined immediately after entry at 25 C, as a function of the size of the donor DNA. Part of the label is found to be acid soluble, part has been incorporated into chromosomal DNA, apparently through reincorporation of degraded donor DNA, and part is found in single strands of length smaller than that of the input donor DNA strands. The last fraction apparently constitutes the precursor for integration of intact donor genetic markers and is referred to as the intact fraction. For large donor DNA the intact fraction contains over 80% of the total intracellular label, but the median strand length has been reduced to 2.2 × 10(6) daltons. For small donor molecules (1 × 10(5) to 6 × 10(5) daltons per strand) the fraction intact increases with donor size from 10 to 50% of the total intracellular label, and the median strand length of this fraction is half that of the donor strands. By combining these results with earlier data on the size dependence of the yield of transformants per unit of total intracellular donor label, we have calculated the probability that a marker in the intact fraction will be integrated, as a function of the length of the donor strand after entry. This probability has a linear dependence on strand length for activities below 40% of maximum, and extrapolates to zero activity at 77,000 daltons per strand.